Perception of the graduates on the process teaching learning in a nursing school - Mori Ramírez, Hallder (2018)
Objective: To determine and interpret the perception of the graduates about the teaching-learning process in a School of Private Nursing. Materials and methods: The research approach is mixed. The design is concurrent according to the time of the methods and quant / which according to the priority. The sample consisted of 120 graduates in the quantitative phase, of which 8 were selected for the qualitative phase. The instrument used in the quantitative phase was a Likert scale of 30 items, validated by expert judgment. For the qualitative phase, a semi-structured interview was used, which allowed grouping the responses into categories. Results: 57% of graduates perceive the teaching - learning process as good, followed by 26% as regular. As for the 4 dimensions, most perceive it as good. In the curricular plan dimension the graduates expressed disagreement regarding the curricular plan, expressed that there is inadequate sequence of the courses, regarding the teaching and learning strategies dimension, the methodology of the sessions was with traditional predominance making use only of multimedia. In the development dimension of teaching-learning activities, they show disagreement with the lack of internship opportunities and with respect to the evaluation dimension of learning and improvement actions expressed to be in agreement with continuous integral evaluations. Conclusions: the majority of graduates perceive the teaching-learning process as good, however, they express dissatisfaction in some categories associated with the dimensions.